Peran Pendidikan Vokasi dalam Melahirkan Wirausahawan (Studi Kasus Peserta Didik SMK Negeri 1 Cikalongkulon Kabupaten Cianjur) - Suherman, Maman; H. Soro, Suharyanto; Ahmad, Irfan; Ningsih, Riyani Fitria; Pawaka, Wahyu (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Vocational education plays a strategic role in preparing competent human resources, particularly in addressing unemployment challenges and creating job opportunities through entrepreneurship. The background of this research is the importance of optimizing vocational education in shaping entrepreneurial generations amidst economic dynamics and labor market demands. This study aims to analyze the role of vocational education at SMK Negeri 1 Cikalongkulon, Cianjur Regency, in producing entrepreneurial generations, identify supporting and inhibiting factors, and provide recommendations for further development. The researches employed a qualitative paradigm, with case study approach. Data collection through observation, interviews, and document studies. The sample selection uses purposive sampling, targeting the school principal, teachers, and students. The research activities were conducted during the 2024 academic year. The findings reveal the following: (1) SMK Negeri 1 Cikalongkulon has implemented vocational education to produce entrepreneurial generations. (2) There are obstacles in the implementation of entrepreneurship education at SMK Negeri 1 Cikalongkulon; (3) The quality of entrepreneurship education at SMK Negeri 1 Cikalongkulon has improved, resulting in competent graduates with entrepreneurial skills. The study also indicates that vocational education at SMK Negeri 1 Cikalongkulon has successfully contributed to producing entrepreneurial generations through a competency-based curriculum, industrial work practice training, and school entrepreneurship programs. However, several challenges remain, including limited facilities and infrastructure and insufficient access to marketing networks. The discussion emphasizes the importance of synergy among schools, businesses, and the government in supporting vocational education programs.